Simulasi Kavitasi Pada Venturi Dengan Menggunakan CFD (Computational Fluid Dynamics) - Mudjijanto Mudjijanto (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2022)
In the piping installation system, the phenomenon of cavitation is often overlooked, while cavitation itself is one of the disadvantages in the piping installation system. For this reason, we conducted a study on the cavitation phenomenon in venturi using Fluent 6.3 software. The fluid pressure entering the venturi comes from pumps that are arranged singly, in series and parallel. For the pressure generated from the pump arrangement as follows single pump 5 psi, 6 psi in series and 11 psi in parallel. The first is to collect data, model on gambit, carry out the meshing process, determine the boundary conditions and run the Fluent 6.3 3D solver. From the simulation, we can see the flow pattern from the characteristics of pressure, velocity, direction, pressure trajectory, and flow velocity trajectory. Cavitation occurs at the venturi neck and turbulent flow occurs at the outlet of the venturi